Trapping Phenomena in InAlN/GaN High Electron Mobility Transistors. (1st January 2018) - Polyakov, A. Y.; Smirnov, N. B.; Shchemerov, I. V.; Yang, Jiancheng; Ren, Fan; Lo, Chien-Fong; Laboutin, Oleg; Johnson, J. W.; Pearton, S. J.
Abstract : Electron trapping-detrapping phenomena were studied for InAlN/GaN high electron mobility transistors (HEMTs) by drain current-drain voltage static and pulsed current voltage (I-V) characteristics, gate current I-Vs, transfer characteristic measurements, current deep level transient spectroscopy (CDLTS) with gate voltage pulsing, and by drain current transient measurements following both drain and gate voltage steps. The electron trapping processes are temperature activated with activation energies of 1.1 eV for drain voltage steps and 1 eV and 0.75 eV for gate voltage steps. Detrapping processes show activation energies 0.9 eV and (0.7–0.75) eV. Drain current transients are accurately described by the sum of two stretched exponents. The amplitudes of CDLTS peaks corresponding to electron trapping and electron detrapping processes show la ogarithmic dependence on the width of the injection pulse, indicating that the traps are related to dislocations.